Border Thinking Reflexivity in City Schools: Possibilities for Teaching in Historically Red States - Carrillo, Juan F.; Karvelis, Noah (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
Historically “Red States” in the United States offer an example of the complex intersections of public education, race, conservative politics, language, and power/resistance which teachers live and work amongst. This article considers these intersections by focusing on the experiences and reflections of a former red state teacher and organizer. Following this, the article situates these reflections within border thinking and borderlands work, attempting to theorize the work of red state teachers. In doing so, the theoretical framework of Border Thinking Reflexivity is offered as a potential way of approaching such experiences and developing deeper understandings of the work of teaching in historically red states.